Factors related to human-vector contact that modify the likelihood of malaria transmission during a contained Plasmodium falciparum outbreak in Praia, Cabo Verde - Stresman, Gillian; DePina, Adilson José; Nelli, Luca; Monteiro, Davidson D. S.; Leal, Silvânia da Veiga; Moreira, António Lima; Furtado, Ullardina Domingos; Roka, Jerlie C. Loko; Neatherlin, John; Gomes, Carolina; Tfeil, Abderrahmane Kharchi; Lindblade, Kimberly A. (Frontiers in Epidemiology, 2022)
Background: Determining the reproductive rate and how it varies over time and space (RT) provides important insight to understand transmission of a given disease and inform optimal strategies for controlling or eliminating it. Estimating RT for malaria is difficult partly due to the widespread use of interventions and immunity to disease masking incident infections. A malaria outbreak in Praia, Cabo Verde in 2017 provided a unique opportunity to estimate RT directly, providing a proxy for the intensity of vector-human contact and measure the impact of vector control measures. Methods: Out of 442 confirmed malaria cases reported in 2017 in Praia, 321 (73%) were geolocated and informed this analysis. RT was calculated using the joint likelihood of transmission between two cases, based on the time (serial interval) and physical distance (spatial interval) between them. Log-linear regression was used to estimate factors associated with changes in RT, including the impact of vector control interventions. A geostatistical model was developed to highlight areas receptive to transmission where vector control activities could be focused in future to prevent or interrupt transmission. Results: The RT from individual cases ranged between 0 and 11 with a median serial- and spatial-interval of 34 days (interquartile range [IQR]: 17-52) and 1347 m (IQR: 832-1985 m), respectively. The number of households receiving indoor residual spraying (IRS) four weeks prior was associated with a reduction in RT by 0.84 (95% confidence interval [CI] 0.80-0.89; p-value <0.001) in the peak- and post-epidemic compared to the pre-epidemic period. Conclusions: Identifying the effect of reduced human-vector contact through IRS is essential to determining optimal intervention strategies that modify the likelihood of malaria transmission and can inform optimal intervention strategies to accelerate time to elimination. The distance within which two cases are plausibly linked is important for the potential scale of any reactive interventions as well as classifying infections as imported or introduced and confirming malaria elimination.